Pacific affairs : Vol. 40, no. 1 & 2 - University of British Columbia (Vancouver : University of British Columbia, 1967)
Includes book reviews and bibliographies.
v. 40, no. 1 & 2
An International Review of Asia and the Pacific
Issues for Feb.-Dec. 1929 called also no. 2-12; issues for Jan. 1930- called also v. 3, no. 1-
Full-text scanned reproductions of back issues of this publication are available to subscribing institutions via the JSTOR World Wide Web site.
Issued also on microform.
Published by: Institute of Pacific Relations May 1928-Dec. 1960; UBC, spring 1961-
Keywords: Pan-Pacific relations -- Periodicals